2005
DOI: 10.1007/s11137-005-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Pd from Spent Fuel: 1. Electrochemical Recovery of Palladium from Nitric Acid Solutions

Abstract: The rate of cathodic deposition of palladium from nitrate solutions at a platinum electrode and the current efficiency of the process were studied as influenced by the concentrations of nitric acid, NaNO 3 , U, and other admixtures. In the range of potential E from +0.5 to +0.25 V, the rate of Pd deposition from 1 M HNO 3 solution was 0.73 0.9 mg cm !2 at current efficiency of about 70%. The degree of palladium recovery by cathodic deposition is more than 99% with the coefficient of separation from a-and b-emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The reduction of HNO 3 is rather complicated and involves several steps in which nitrous acid is one of several intermediate N(III) species that have been identified [44]. The current for the cathodic reaction is divided between the reduction of HNO 3 and the formation of H 2 [45]. In the anodic equation m is the average number of holes that are required to dissolve one silicon atom.…”
Section: Methods Ii: the Fabrication Of μS-si From (1 1 0) Si By Two ...mentioning
confidence: 99%
“…The reduction of HNO 3 is rather complicated and involves several steps in which nitrous acid is one of several intermediate N(III) species that have been identified [44]. The current for the cathodic reaction is divided between the reduction of HNO 3 and the formation of H 2 [45]. In the anodic equation m is the average number of holes that are required to dissolve one silicon atom.…”
Section: Methods Ii: the Fabrication Of μS-si From (1 1 0) Si By Two ...mentioning
confidence: 99%
“…Recovery of valuable PGMs from nuclear HLLW was extensively studied [65][66][67][68][69][70] in the last two decades with particular interest in the separation of palladium. Several authors have reported the electrochemical recovery of PGMs from nitric acid medium [71][72][73][74][75]. Kirshin and Pokhitonov [73] studied the electrolytic recovery of palladium from nitric acid solutions and reported the efficiency of the process in the presence of HNO 3 , NaNO 3 , uranium, and other admixtures.…”
Section: Platinum Group Metalsmentioning
confidence: 99%
“…Several authors have reported the electrochemical recovery of PGMs from nitric acid medium [71][72][73][74][75]. Kirshin and Pokhitonov [73] studied the electrolytic recovery of palladium from nitric acid solutions and reported the efficiency of the process in the presence of HNO 3 , NaNO 3 , uranium, and other admixtures. Varentsov and Varentsova [74] reported the electrodeposition of rhodium on carbon fiber electrodes from nitric acid and confirmed that speciation of rhodium strongly affects the deposition behavior.…”
Section: Platinum Group Metalsmentioning
confidence: 99%